Oligarchy and Political Dynasties' Impact on Democracy - Purnama, Arie; Poyo, M.; Hernawan, Wawan (Interaction Communication Studies Journal, 2025)
This study aims to analyze the phenomenon of oligarchy in Indonesian politics, focusing on how political power is concentrated in the hands of economic elites and the resulting implications for democratic governance. It specifically explores the role of political parties and government policy under President Jokowi in reinforcing oligarchic structures. A descriptive qualitative method with a literature review approach is employed in this study. Data is gathered from academic publications, news reports, books, and legal documents to critically assess the patterns and impact of oligarchic dominance in Indonesia’s political system. Political parties in Indonesia often operate as tools for oligarchs to maintain their power and influence. Although President Joko Widodo was initially viewed as a reformist leader, his administration has become increasingly aligned with oligarchic interests. Legislative changes, including the revision of the Corruption Eradication Commission Law (KPK Law), the enactment of the Omnibus Law on Job Creation, and the amendments to the Criminal Code (KUHP), have provided legal protection and advantages to political and economic elites. To reduce the influence of oligarchy in politics and ensure that power genuinely lies with the people, Indonesia must adopt several reform strategies. These include strengthening democratic institutions, enhancing transparency in political financing, promoting accountability in governance, and increasing meaningful public participation. The future of democracy in Indonesia will depend on the country’s ability to restrain oligarchic power and uphold democratic values rooted in public accountability and civic engagement.